Uji Kepolaran Ekstrak Buah Impor Menggunakan Alat Sederhana Berbasis Listrik untuk Pembelajaran Kimia - Regina Gresella Br Panjaitan; Agnes Yuniarty Simbolon; Dwi Rahmanisa; Efrio Angelina Sitio; Gavril Orlando Tumio Manalu; Rode Juwita Sinaga; Vebilla May Ningsih; Iis Siti Jahro (Jurnal Sains dan Ilmu Terapan, 2025)
Polarity is an essential concept in chemistry, but many students struggle to grasp it, necessitating the use of a simple learning medium. This study aims to examine the polarity levels of extracts from ten imported fruits, including Fuji apple, kiwi, strawberry, Sunkist orange, grape, pear, date, blueberry, cherry, and dragon fruit, using a static electricity-based device. The device was created using simple materials, making it practical for use in chemistry lessons. Its working principle is based on the deflection of liquid droplets, which are influenced by static electric charges on mica. The results showed that most extracts experienced varying degrees of deflection. Strawberry, pear, and kiwi exhibited strong deflection due to the presence of polar compounds, while apple, cherry, and grape demonstrated moderate deflection. Blueberry could not be tested due to its high viscosity. This study presents a straightforward learning tool to help students better understand the polarity of covalent compounds, providing an accessible approach to learning complex chemistry concepts.